The Microcirculation Is Unchanged in Neonates with Severe Respiratory Failure after the Initiation of ECMO Treatment - Anke P. C. Top; Erik A. B. Buijs; Patrick H. M. Schouwenberg; Monique van Dijk; Dick Tibboel; Can Ince (Critical Care Research and Practice, 2012)
Purpose. Venoarterial extracorporeal membrane oxygenation (VA-ECMO) is known to improve cardiorespiratory function and outcome in neonates with severe respiratory failure. We tested the hypothesis that VA-ECMO therapy improves the microcirculation in neonates with severe respiratory failure. Methods. This single-center prospective observational pilot study took place in an intensive care unit of a level III university children’s hospital. Twenty-one-term neonates, who received VA-ECMO treatment, were included. The microcirculation was assessed in the buccal mucosa, using Orthogonal Polarization Spectral imaging, within 24 hours before (T1) and within the first 24 hours after initiation of ECMO treatment (T2). Data were compared to data of a ventilated control group (𝑁=7). Results. At baseline (T1), median functional capillary density (FCD), microvascular flow index (MFI), and heterogeneity index (HI) did not differ between the ECMO group and the control group. At T2 the median FCD was lower in the control group (median [range]: 2.4 [1.4–4.2] versus 4.3 [2.8–7.4] cm/cm2; P value <0.001). For MFI and HI there were no differences at T2 between the two groups. Conclusion. The perfusion of the microcirculation does not change after initiation of VA-ECMO treatment in neonates with severe respiratory failure.